AGE-DEPENDENT FEATURES OF THE BONE MARROW RESPONSE TO TOXICOGENIC LIVER FIBROSIS IN THE EXPERIMENT - Ivanov , Ievgen; Bondar , Anastasiia; Bozhkov , Anatoly (Collection of scientific papers «ΛΌГOΣ», 2024)
Liver fibrosis has been shown to affect bone marrow cell morphotypes. This study investigated the response of bone marrow cells to fibrosis. Bone marrow cells from rats of different ages were the object of study. It was shown that the proliferative activity of bone marrow cells in animals with Cu-induced fibrosis was significantly lower than in animals with CCl4-induced liver fibrosis. Bone marrow plays an important role in the development of liver fibrosis.